Analisis Penggunaan Labelisasi Halal pada Produk Minuman Mixue dalam Meningkatkan Kepecayaan Konsumen Muslim di Kota Medan - Rosmaliza Lubis; Muhammad Yafiz (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to analyze the level of trust of Muslim consumers in Medan City towards Mixue beverage products before and after the application of halal labeling. The research method used is a qualitative method with a descriptive analysis approach. The results of this study indicate that the halal label is very important for Muslim consumers in choosing and buying products, including Mixue beverage products. This is because it is believed that products that have received the halal label have gone through a strict certification process and are in accordance with Islamic sharia principles. In addition, the halal label also gives confidence to Muslim consumers that the product is safe and halal for consumption. Apart from the halal label, this study also found that other factors such as product quality, price, and promotion also influence the decision of Muslim consumers to buy Mixue drinks. However, overall the halal label remains an important factor that producers must pay attention to in marketing Mixue beverage products to Muslim consumers in Medan City. Overall, this research provides useful information for producers in developing appropriate marketing strategies for Mixue beverage products in Medan City.